A single centre service evaluation of 53 MRONJ cases - Millicent Forrest; Sanford Grossman; Noha Seoudi; Edmund Bailey; Rishi Bhandari; Leo Cheng; Judith Jones; Zoe Killick; Mohammed Dungarwalla (Advances in Oral and Maxillofacial Surgery)
Medication-related osteonecrosis of the jaw (MRONJ) is a significant complication associated with antiresorptive or antiangiogenic medications, particularly bisphosphonates and denosumab, commonly used in the management of osteoporosis and metastatic bone disease.This retrospective service evaluation assessed treatment modalities and outcomes of MRONJ patients treated at the Royal London Dental Hospital (RLDH) between 2018 and 2023. A cohort of 53 patients, primarily oncology patients, were analysed, with 60 % of MRONJ sites presenting in the posterior mandible. Tooth extractions were identified as a leading precipitating factor in MRONJ development, while poor oral hygiene exacerbated disease progression.Management strategies included conservative and operative interventions, with surgical debridement yielding a 70.6 % success rate in healing. Antibiotic therapy was prescribed in 50 % of stage 1 patients despite a lack of infection, highlighting the need to audit such use given the lack of evidence outside infection in stages 2 and 3.This evaluation highlights the importance of preventive dental care, patient-centred personalised treatment planning, and the role of surgical interventions in MRONJ management.